An African bat in Europe, Plecotus gaisleri: Biogeographic and ecological insights from molecular taxonomy and Species Distribution Models. Issue 12 (29th April 2020) - Ancillotto, Leonardo; Bosso, Luciano; Smeraldo, Sonia; Mori, Emiliano; Mazza, Giuseppe; Herkt, Matthias; Galimberti, Andrea; Ramazzotti, Fausto; Russo, Danilo
Abstract: Because of the high risk of going unnoticed, cryptic species represent a major challenge to biodiversity assessments, and this is particularly true for taxa that include many such species, for example, bats. Long‐eared bats from the genus Plecotus comprise numerous cryptic species occurring in the Mediterranean Region and present complex phylogenetic relationships and often unclear distributions, particularly at the edge of their known ranges and on islands. Here, we combine Species Distribution Models (SDMs), field surveys and molecular analyses to shed light on the presence of a cryptic long‐eared bat species from North Africa, Plecotus gaisleri, on the islands of the Sicily Channel, providing strong evidence that this species also occurs in Europe, at least on the islands of the Western Mediterranean Sea that act as a crossroad between the Old Continent and Africa. Species Distribution Models built using African records of P. gaisleri and projected to the Sicily Channel Islands showed that all these islands are potentially suitable for the species. Molecular identification of Plecotus captured on Pantelleria, and recent data from Malta and Gozo, confirmed the species' presence on two of the islands in question. Besides confirming that P. gaisleri occurs on Pantelleria, haplotype network reconstructions highlighted moderate structuring between insular and continental populations of this species. Our results remark the role of Italy as a bat diversity hotspot in the Mediterranean and also highlight the need to include P . gaisleri in European faunal checklists and conservation directives, confirming the usefulness of combining different approaches to explore the presence of cryptic species outside their known ranges—a fundamental step to informing conservation. Abstract : Here, we combine Species Distribution Models, field surveys, and molecular analyses to shed light on the long‐debated presence of a cryptic long‐eared bat species from North Africa, Plecotus gaisleri, on the islands of the Sicily Channel, providing strong evidence that this species also occurs in Europe, at least on the islands of Western Mediterranean that act as a crossroad between the Old Continent and Africa.